Malationa, malation or malatiom? Denominative variation in the process of creating a bilingual glossary in the area of pesticide chemistry - Souza, José Victor de (2022)
This research aims to meet the needs of a terminological study in the field of pesticide chemistry, since Brazil is one of the most productive countries in agricultural activities in the world. The study starts from the translation and terminological problem of the area, previously observed by Pinto and Lima (2018) and Souza (2019), and proposes the search of terms in the area for the elaboration of a Portuguese ⇔ English glossary. The research is based on the areas of Terminology (Krieger & Finatto, 2004; Finatto, 2004; Bevilacqua, 2013), Chemistry (Abakerli et al., 2003) and Corpus Linguistics (Sardinha, 2000; Tagnin, 2002). In this paper, we demonstrate the process of creating the study corpus, as well as the criteria for selecting candidates for terms in English. In order to illustrate occurrences of denominative variation during the selection of equivalents in Portuguese, we present the steps used for the selection of the most appropriate term among the Portuguese vernacular variants ‘malation’, ‘malationa’, and ‘malatiom’, and show why ‘malation’ is the form chosen, taking into account its absolute frequency, Average Reduced Frequency, coefficient of variation, number of results in web research, as well as linguistic, conceptual and normative criteria. We concluded that the partnership between computerized tools and specialized knowledge, both in linguistics and in chemistry, brought benefits to the discussion that would not be achieved only through computational calculations